Kajian Industri Minuman Teh Sebagai Minuman Halal di Indonesia: Kualitas Sensori dan Preferensi Konsumen - Septariawulan Kusumasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The tea beverage industry in Indonesia is a significant contributor to the national economy and is a popular commodity for domestic consumption. The objective of this study is to analyze the tea beverage sector in Indonesia, specifically in terms of its status as a halal beverage. The study will primarily focus on evaluating the sensory quality of the tea and understanding consumer preferences. A descriptive qualitative methodology was employed to choose four widely recognized packaged tea brands. The sensory study was conducted using hedonic rating tests to ascertain the optimal product quality and the products most favored by the panelists. The study's findings indicate that the four brands of packaged tea comply with the regulations set by LPPOM and BPJPH regarding halal certification. Regarding sensory quality, Teh Pucuk and Frestea exhibit a high level of consumer acceptability, with overall parameter ratings of 5.16 and 5.44, respectively (indicating a moderate likeness). Teh Pucuk stands out for its exceptional freshness and taste, Teh Kotak is known for its consistent quality and enticing aroma, Teh Botol is renowned for its strong brand confidence, and Frestea is distinguished by its jasmine aroma and convenient packaging. Manufacturers who can uphold product quality, foster innovation, and execute effective promotions will experience greater ease in acquiring consumer preferences and enhancing consumer loyalty.